2014
DOI: 10.1007/s00251-014-0799-9
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoiesis in the equine fetal liver suggests immune preparedness

Abstract: We investigated how the equine fetus prepares its pre-immune humoral repertoire for an imminent exposure to pathogens in the neonatal period, particularly how the primary hematopoietic organs are equipped to support B cell hematopoiesis and immunoglobulin (Ig) diversity. We demonstrated that the liver and the bone marrow at approximately 100 days of gestation (DG) are active sites of hematopoiesis based on the expression of signature mRNA (c-KIT, CD34, IL7R, CXCL12, IRF8, PU.1, PAX5, NOTCH1, GATA1, CEBPA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
(125 reference statements)
1
14
0
Order By: Relevance
“…However, immunoglobulin diversity is generated differently among species. Previously, we observed that although there was a bias for IGLV segment use in fetal life, the equine fetus used a broader range of IGLV segments than the adult horse (Battista et al, 2014 and Tallmadge et al, 2014). In this study, we wanted to learn (1) if there were differences in IGLV segment used between CD5 hi and CD5 lo B cells; and (2) if trends in IGLV segment use in CD5 hi B cells could explain differences in combinatorial diversity previously observed between the equine fetus and adult horse (Tallmadge et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, immunoglobulin diversity is generated differently among species. Previously, we observed that although there was a bias for IGLV segment use in fetal life, the equine fetus used a broader range of IGLV segments than the adult horse (Battista et al, 2014 and Tallmadge et al, 2014). In this study, we wanted to learn (1) if there were differences in IGLV segment used between CD5 hi and CD5 lo B cells; and (2) if trends in IGLV segment use in CD5 hi B cells could explain differences in combinatorial diversity previously observed between the equine fetus and adult horse (Tallmadge et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Different types of lymphoid tissues were sampled by age groups because of their availability and accessibility. Fetal liver leukocytes were obtained as previously described (Battista et al, 2014). In brief, 2 adult mares (1 Thoroughbred and 1 Warmblood) at the Cornell Equine Park were bred, abortions were chemically induced with prostaglandin injections (Lutalyse, Pfizer, New York, NY) at approximately 100 days of gestation (102–105DG) (Douglas and Ginther, 1976), and the fetal livers dissected and processed (see below) within an hour of abortion.…”
Section: Methodsmentioning
confidence: 99%
“…29–31 The cell suspension was carefully layered over density gradient medium (density, 1.077), d which was then centrifuged e at 700 × g ; cells at the interface were harvested, washed in PBS solution–BSA, and incubated for 30 minutes with anti-canine CD34 antibody f (dilution, 1:10). 32,33 Cells were washed several times, resuspended in PBS solution–BSA with 2mM EDTA, g and incubated with immunomagnetic microbead-conjugated rat anti-mouse IgG1. h The CD34 + cells were obtained by passing the microbead-labeled cells through a cell separation column i placed in a magnetic field h that allowed retention of the target cells.…”
Section: Methodsmentioning
confidence: 99%
“…30,31,33,3640 These included anti-canine CD34 (clone 1H6), a anti-equine CD19 (clone cz2.1), p anti-human IgM (clone CM7) ii for cytoplasmic and surface IgM, anti-human E2A (V-18), jj anti-human EBF (C-8), jj anti-human CD29 (4B4), a anti-equine CD90 (DH24A), kk and anti-equine CD14 (clone 105). ll To measure the specificity and yield of the sorted BM cell precursors by use of the anti-canine CD34 monoclonal antibody, an anti-equine CD34 monoclonal antibody was developed by a company mm and applied to the BM-sorted solutions.…”
Section: Methodsmentioning
confidence: 99%
“…With increasing doses of MMO, cortical thymocytes increased, which demonstrated that MMO could activate the immune response and reduce the thymus injury induced by CTX [30]. The liver is the central hub of the body's metabolism, with functions such as detoxification and hematopoiesis [31]. To investigate whether there was an effect on the liver after using immunosuppressive agents and MMO, the histological structure of the mouse liver was observed.…”
Section: Morphological Observations Of Mouse Organsmentioning
confidence: 99%